Fields of applied psychology - "Anastasi, Anne" (Tokyo, 1964)
This revision has retained the objectives and basic approach of the first edition. Yet within that framework, it is largely a new book. In practically all fields of applied psychology, the mid-sixties marked the beginning of an era of unprecedented activity. This growth is reflected in the present edition insofar as about 70% of the references now cited postdate the 1964 edition.
Keywords: Psychology-Applied